HPV type‐specific trends in cervical precancers in the United States, 2008 to 2016. Issue 2 (26th September 2022) - Gargano, Julia W.; McClung, Nancy; Lewis, Rayleen M.; Park, Ina U.; Whitney, Erin; Castilho, Jessica L.; Pemmaraju, Manideepthi; Niccolai, Linda M.; Brackney, Monica; DeBess, Emilio; Ehlers, Sara; Bennett, Nancy M.; et al.
Abstract: Declines in cervical intraepithelial neoplasia grades 2 to 3 and adenocarcinoma in situ (CIN2+) observed among young women suggest impact from human papillomavirus (HPV) vaccination. To further evaluate vaccine impact including cross‐protection and type replacement, we described high‐risk (HR)‐HPV type‐specific cervical precancer incidence rates among women aged 20 to 39 years, 2008 to 2016. We analyzed cross‐sectional population‐based data on 18 344 cases of CIN2+ from a 5‐site surveillance system. Diagnostic specimens were tested for individual HPV types, including 14 HR‐HPV types (HPV16/18/31/33/35/39/45/51/52/56/58/59/66/68). We estimated age‐specific annual HR‐HPV type‐specific CIN2+ incidence per 100 000 screened women for individual types, vaccine HR‐HPV types (HPV16/18) and nonvaccine HR‐HPV types (non‐HPV16/18). We evaluated trends using average annual percent changes (AAPC) and 95% confidence intervals (CI), and estimated total declines by comparing 2015‐2016 to 2008‐2009 using incidence rate ratios. Among 20‐24‐year‐olds, HPV16/18‐CIN2+ declined from 2008 through 2016 (AAPC: −21.3%, 95% CI: −28.1%, −13.8%), whereas no trend was observed for non‐HPV16/18‐CIN2+ (AAPC: −1.8%, 95% CI: −8.1%, 4.9%). After 2010, CIN2+ among 20‐24‐year‐olds was more often caused by nonvaccine vs vaccine HR‐HPV types. No significant declining trends were observed in older age groups. In 2015‐2016 compared with 2008‐2009, HPV16‐CIN2+ declined 78%, HPV18‐CIN2+ 72% and HPV31‐CIN2+ 51% among 20‐24‐year‐olds; no increases were observed in type‐specific CIN2+ incidence. Among 25‐29‐year‐olds, HPV16‐CIN2+ declined 18%; CIN2+ attributed to seven nonvaccine types increased significantly. No significant declines were observed in older groups. Significant declines in HPV16/18‐CIN2+ in 20‐24‐year‐olds and HPV16‐CIN2+ in 25‐29‐year‐olds corroborate impact of HPV vaccination. A declining trend in HPV31‐CIN2+ is consistent with cross‐protection from vaccination. Abstract : What's new? While vaccination against human papillomavirus (HPV) likely is responsible for recent declines in the incidence of cervical intraepithelial neoplasia grade 2 or higher (CIN2+) in young women, the true impact of vaccination on cervical precancer remains uncertain. Here, the authors examined trends in HPV‐type specific CIN2+ and CIN3+ in women in the United States. Analyses show that HPV vaccination had a strong and specific role in reducing cervical precancer incidence caused by high‐risk HPV types 16 and 18 among young women. A decline in HPV31 further suggests cross‐protection against a high‐risk HPV type not targeted by vaccination.